4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y
4(3x-8y = 24) 12x+32y = 96 Multiply all terms in the first equation by 4: 12x-32y = 96 12x+32y = 96 Add both equations together: 24x = 192 Divide both sides by 24 to find the value of x: x = 8 Substitute the value of x into the original equations to find the value of y: Therefore: x = 8 and y = 0
32
We have 3x+9y=36, or equivalently 12x+36y=144. We also have 12x+4y=18, so subtracting these we have 32y=126 or y=63/16. Substituting this into our original equation leaves 3x=36-9*63/16 or x = 12-3*63/16 = 3/16. So: x=3/16, y=63/16
2y + 3 = 42y = 4 - 32y = 1divide both sides of the equation by 22y/2 = 1/2y = 1/2 in fractionory = 0.50 in decimal
4x-y=32y=-2x+70 Try rearraging it. If they're all equal, then the order does not matter.2x+70=4x-y=32y-4x,-4x,+y,+y-2x+70=33y-x+35=33y
4(3x-8y = 24) 12x+32y = 96 Multiply all terms in the first equation by 4: 12x-32y = 96 12x+32y = 96 Add both equations together: 24x = 192 Divide both sides by 24 to find the value of x: x = 8 Substitute the value of x into the original equations to find the value of y: Therefore: x = 8 and y = 0
39
The expression can be factored as -12x + 32y -16z = 4(-3x + 8y - 4z) but a slightly improved presentation would be to extract -4 from the original expression. So, -12x + 32y -16z = -4(3x - 8y + 4z)
27
80x+32y=1280
32
We have 3x+9y=36, or equivalently 12x+36y=144. We also have 12x+4y=18, so subtracting these we have 32y=126 or y=63/16. Substituting this into our original equation leaves 3x=36-9*63/16 or x = 12-3*63/16 = 3/16. So: x=3/16, y=63/16
2y + 3 = 42y = 4 - 32y = 1divide both sides of the equation by 22y/2 = 1/2y = 1/2 in fractionory = 0.50 in decimal
it equals 18 times 18. 18 times 18 equals 324. 324 is your answer.
18 teaspoons equals 6 tablespoons.
3 divided by 18 equals what = 0.16666666666666666